Change and continuity in children's services - Parker, R. A. (Roy Alfred), 1931- (Policy Press, 2015)
There are, sadly, children whose lives are severely blighted by abuse, by neglect and by separation from their parents. Ways have been devised to protect and care for them. Some have been encouragingly enlightened while others have been deeply misguided. These essays describe and explain the significant political, economic, legal and ideological factors that have shaped this history from the mid-1850s up to the present day. In this, as much emphasis has been given to accounting for the unchanging nature of certain problems, issues and assumptions as to what has changed: hence the title.